Discovery of a radio nebula around PSR J0855−4644. (20th March 2018) - Maitra, C; Roy, S; Acero, F; Gupta, Y
Abstract: We report the discovery of a diffuse radio emission around PSR J0855−4644 using an upgraded GMRT ( uGMRT ) observation at 1.35 GHz. The radio emission is spatially coincident with the diffuse X-ray pulsar wind nebula (PWN) seen with XMM–Newton but is much larger in extent compared to the compact axisymmetric PWN seen with Chandra . The morphology of the emission, with a bright partial ring-like structure and two faint tail-like features strongly resembles a bow shock nebula, and indicates a velocity of 100 km s −1 through the ambient medium. We conclude that the emission is most likely to be associated with the radio PWN of PSR J0855−4644. From the integrated flux density, we estimate the energetics of the PWN.